The shibolets of the procés: Vilajosana on the right to decide - Moreso, Josep Joan (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
In this comment, the articulated defence by Vilajosana (2020) of a right to decide of the Catalan citizens for seceding from Spain is discussed. It is argued that such right, understood as a claim-right, which involves correlative duties, is not legal in accordance with the Spanish Constitution, because at most the Spanish Constitution authorize a liberty-right, subjected to the stipulated requirements by the Constitution. It is also defended that such right is not legitimate, from the political philosophy point of view, because there is no conceptually plausible way to attribute the right to a subset of citizens in one State and not to other subset, including the subset integrated by all the citizens of the State, given that every set is a subset of itself.
Keywords: Vilajosana; Catalonia; secession; right to decide; plebiscitary strategy